2010
DOI: 10.1158/1535-7163.mct-09-0696
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to the Aromatase Inhibitor Letrozole Is Prolonged After a “Break” in Treatment

Abstract: Using a hormone-dependent xenograft model, we established that loss of response to letrozole was accompanied by upregulation of the Her-2/mitogen-activated protein kinase (MAPK) pathway and downregulation of estrogen receptor α (ERα) and aromatase activity. In our previous study, we showed that stopping letrozole treatment or adding trastuzumab could reverse acquired resistance. In this study, we compared the effects of intermittent letrozole treatment and switching treatment between letrozole and trastuzumab … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 25 publications
2
42
0
Order By: Relevance
“…This has also been confirmed in xenograft models where adaption of the cells to low estrogen levels is accompanied by up-regulation of HER-2/neu and downregulation of ER and aromatase activity [12,13]. Thus, increased expression or activation of growth factor receptors and cross-talk between ER-and alternate growth factor signaling pathways may cause endocrine resistance [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 90%
“…This has also been confirmed in xenograft models where adaption of the cells to low estrogen levels is accompanied by up-regulation of HER-2/neu and downregulation of ER and aromatase activity [12,13]. Thus, increased expression or activation of growth factor receptors and cross-talk between ER-and alternate growth factor signaling pathways may cause endocrine resistance [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 90%
“…Letrozole and D 4 A for injection were prepared using 0.3% weight per volume (w/v) hydroxypropyl cellulose (HPC) in 0.9% w/v NaCl solution and injected s.c. five times weekly. The doses of letrozole (10 mg/day) and D 4 A (100 mg/day) used are as previously determined and reported (Sabnis et al 2008(Sabnis et al , 2010.…”
Section: Tumor Growth In Ovx Female Athymic Nude Micementioning
confidence: 99%
“…Several reports suggest that a bidirectional cross talk between ER, HER-2, and other members of the EGFR family play a key role in the resistant model systems (Osborne et al 2005, Sabnis et al 2005, Arpino et al 2008 and that inhibition of only one pathway leads to the activation of the other. Loss of response to letrozole was accompanied by up-regulation of the HER-2/mitogen-activated protein kinase pathway and down-regulation of ER and aromatase activity (Sabnis et al 2010). In addition, preclinical models with trastuzumab (Sabnis et al 2009), gefitinib (Massarweh et al 2006), or lapatinib (Xia et al 2006) have consistently shown that inhibition of the growth factor activity in endocrineresistant cells could be associated with an adoptive increase in ER signaling and subsequent restoration of sensitivity to endocrine treatment.…”
Section: Discussionmentioning
confidence: 99%